Mismatch negativity in children with cochlear implant - Hamid, Mai; Kotait, Mona Ahmed; Kolkaila, Enaas Ahmad (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Cochlear implant provides a great opportunity for children with severe to profound sensorineural hearing loss to restore normal hearing. Identifying mismatch negativity (MMN) in cochlear implant recipients helps to assess the role of central auditory structures in processing speech stimuli in those patients. The objective of the present study is to evaluate tone and speech discrimination in cochlear implanted children using mismatch negativity test. Methods: MMN was recorded in 35 children. They were divided into two groups. Control group consisted of 15 normal hearing children, their age ranged from 3-11 years. Study group consisted of 20 children fitted with unilateral CI, and their age matched the control group. Two oddball paradigms were used; the first was tone bursts (1000 Hz as standard stimulus and 1050 Hz as deviant stimulus). The second was synthesized speech stimuli (/da/ as standard stimulus and /ga/ as deviant one). Both paradigms were presented at 75dB SPL. Results: All cochlear implanted children included showed MMN on using both oddball paradigms. Comparing results of both groups revealed statistically significant differences in MMN latency and amplitude. There was a significant positive correlation between MMN latencies and the implantation age as well as the duration of hearing loss before implantation. Conclusions: MMN provides an objective tool to assess the auditory discrimination abilities in cochlear implanted children which may help in their rehabilitation and also in the optimum setting of their devices.